ANALISIS SEMIOTIKA TENTANG NILAI-NILAI PROTAGONIS PADA TOKOH ARTHUR DI FILM JOKER (2019) - Sandi Putra; Sandi Justitia Putra; Irma Elmira Husbuyanti (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2024)
Film is a tool used to convey messages to the audience with a number of interpretations. The aim of this research is to find the meaning of denotation, connotation and myth regarding the values of the protagonist in the film Joker. Roland Barthes' semiotic analysis is an analytical technique that researchers use. Researchers used video recordings of the film Joker as a data source and then continued by selecting several scenes related to the values of the protagonist Joker. The data was then analyzed using Roland Barthes' semiotics to look for the meaning of denotation, connotation and myth in the scene. The results of this research show that 1) The denotational meaning represented in the film Joker is shown through certain scenes of the actions carried out by Arthur which are often considered unnatural by other people but have a good meaning which represents the main character Arthur as a protagonist figure or character who defends justice; 2) Representation of connotative meaning is shown in the transformation of the protagonist's identity into an antagonist character which reflects the existence of a character with a new story as a defender of justice for oppressed people named Joker; 3) The representation of the meaning of the myth is depicted in Arthur's refusal to own weapons, which symbolizes moral integrity and refusal to commit acts of violence even when there is an opportunity for revenge.